The relationships between isometric muscle strength and respiratory functions of the Turkish National Paralympic Goalball Team - Balci, A.; Akinoglu, B.; Kocahan, T.; Hasanoglu, A. (Journal of Exercise Rehabilitation, 2021)
Goalball is a unique sport for only blind and visually disabled people to prevent physical inactivity and its harmful consequences. Determining the profile of physical fitness parameters and their relationship is crucial for all sports discipline. The purpose of the study is to determine the characteristics and the relationship between isometric muscle strength and respiratory functions. A total of 14 (10 female, four male athletes) goalball athletes were included in the study. Upper-extremity, lower-extremity and trunk isometric muscle strength and pulmonary function tests measurements were performed to the athletes on two different days. The relationship between parameters was evaluated by Spearman correlation test. Strength and pulmonary function parameters were higher in male athletes (P<0.05). A medium/strong/very strong correlation was found between respiratory function and upper extremity isometric muscle strength (r=0.529-0.917, P<0.05). A moderate/strong correlation was found between lower extremity isometric muscle strength and respiratory function (r=0.534-0.867, P<0.05). A moderate correlation was found between trunk isometric muscle strength and respiratory function (r=0.538-0.640, P<0.05). It was seen that respiratory functions were associated with upper-lower extremity and trunk muscle strength. With this result, the idea arises that strength exercises can affect the improvement of respiratory function in individuals with disabilities, which is very important for both overall health and sports performance.